Political ideology in Britain - Leach, Robert 1941- (Palgrave Macmillan, 2009)
Evaluating the changing role of ideology in contemporary British politics, this book describes contending ideologies and emphasizes their relations to the ideas, institutions, and practices of British political life. Chapters describe the content and applications of liberalism, conservatism, socialism, nationalism, fascism and racism, feminism, Green ideology, the New Right, and New Labour. Specifically British variants are compared and contrasted with international currents of thought. Leach teaches business at Leeds Metropolitan University.
Keywords: Geschichte; Ideologie; Politisches System; Politische Wissenschaft; Ideology -- Great Britain; Political science -- Great Britain; Right and left (Political science); Partei; Großbritannien